Spatial price transmission of soaring milk prices from global to domestic markets - Acosta, Alejandro; Ihle, Rico; Robles, Miguel (Wiley, 2014)
Milk has become one of the most volatile agricultural commodities in the international market. High volatility of commodity prices and their implications for food security are clearly among the most important issues facing policy makers today. Thus, a deeper understanding of the magnitude, speed, and symmetry to which global milk prices are being transmitted to domestic prices at the farm gate level is a fundamental factor in the design of appropriate policy measures oriented to reduce not only the level of milk price volatility, but also poverty and food insecurity. The purpose of this article is therefore to assess the dynamics of the relationship between global and domestic milk prices. [Econ Lit Classifications: Q11, Q13, Q17].